Prevalence and Morphometry of Arcuate Foramen in Atlas Vertebrae in Pakistanis (Medical Forum Monthly, 2024)
Objective: To assess the prevalence and morphometry of arcuate foramen and comparison with native foramen transversarium in atlas vertebrae of Pakistani population.Study Design: Descriptive / observational study.Place and Duration of Study: This study was conducted at Anatomy department, Sheikh Zayed Medical College Rahim Yar Khan and Wah Medical College Wah Cantt. during a period of two years from Jan 2012 to Dec. 2013.Materials and Methods: The study included 150 dried human atlas vertebrae. Prevalance of complete arcuate foramina (CAFs) in atlas vertebrae were noted and its anteroposterior and superoinferior diameters were measured by vernier calipers with accuracy of 0.01 mm. Size and shape of CAFs were compared with native foramina transversaria (NFTs).Results: Out of 150 atlas vertebrae, 13 (8.66%) showed CAF. The mean anteroposterior diameter of the right CAF was 6.71 mm and that of left was 6.76 mm. The mean superoinferior diameter was 5.07 mm on the right and on left side it was 5.22 mm. The mean cross-sectional area of CAFs was 26.74 mm2 and 27.77 mm2 for the right and left sides respectively. The mean cross-sectional area of the right NFTs was 34.86 mm2, while the mean area for the left was 35.31 mm2.Conclusion: This study provides information on the morphometry of arcuate foramen and ipsilateral native foramina transversaria (NFTs) and their implications. The observation that CAFs are smaller than ipsilateral NFTs suggests that they are an important cause of vertebral artery compression syndromes and needs careful investigations. Knowledge of CAF may help the surgeons undertaking procedures in the C1 region.